The gut microbiota-bile acid axis links the positive association between chronic insomnia and cardiometabolic diseases - Zengliang Jiang; Lai-bao Zhuo; Yan He; Yuanqing Fu; Luqi Shen; Fengzhe Xu; Wanglong Gou; Zelei Miao; Menglei Shuai; Yuhui Liang; Congmei Xiao; Xinxiu Liang; et al. (Nature Communications, 2022)
Chronic insomnia is associated with cardiometabolic diseases. Here, in two clinical cohorts (n = 7,931), authors show that gut microbiota-bile acid axis may be an intervention target to attenuate the impact of chronic insomnia on cardiometabolic health.